Pembelajaran Pantun Berbasis Proyek dengan Model ADDIE untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas VII SMP Negeri 6 Medan - Asnidar Asnidar; Yulia Arfanti; Suyadi Suyadi (Mahesa Research Center, 2026)
This study aims to develop a Project-Based Learning (PjBL) model for teaching pantun (traditional Malay poetry) to enhance the interest and learning outcomes of seventh-grade students at SMP Negeri 6 Medan. The research employs a Research and Development (R&D) approach using the ADDIE model. Thirty students participated in creative projects such as digital pantun, short videos, and interactive performances. Data were collected through observation, questionnaires, tests, and interviews. Results indicate a significant increase in student interest and an improvement in average scores from 65.4 (pre-test) to 85.2 (post-test). Qualitative analysis revealed higher motivation and active engagement among students. The findings suggest that PjBL is effective not only for teaching traditional literature but also for fostering creativity, collaboration, and 21st-century skills. The model can be adapted within the Merdeka Curriculum to support more contextual and meaningful learning.